A Study on Opium and Drugs in Namsai District, Arunachal Pradesh: With Special Reference to Emphum Village - Singkai, Chow Nakunand; Tripathy, Biplab; Mondal, Tanmoy (Integrated Journal for Research in Arts and Humanities, 2023)
The Namsai district is the land of multiple tribes‟ viz. Tai-Khamtis, Mishmis, Singphos and some other sub tribes which lie in the eastern parts of Arunachal Pradesh. In this remote and near China-Myanmar border, the district is facing a big problem of drugs for long period of time. Since a long, the poppy had associated with the life of the people due to some myths which is a prime cause of present of opium in this region. Opium is an alkaloid derivative of Papaver somniferum commonly known as poppy. The other derivatives of this plant are Heroin, Morphine, Codine and Papaverum, ganja. Derivatives like Morphine have long been used as medicine. Ages of male addicts are from 20 years onwards. Addiction cause varies. It is seen among youngsters mostly. Opium is sold as per tola, roughly equivalent to 10 grams. This paper attempts to explore the reasons responsible for drug addiction. The reasons are examined in relation to eight hypothetical factors, such as peer group, enjoyment, frustration/tension, sufficient leisure, and excess pocket money, imitation of family elders, easy availability and curiosity. Moreover, the remedial measures undertaken by the Drug De-addiction centres and their benefits among the addicts are also analyzed.